Exploring moral distress in potential sibling stem cell donors - Begley, Ann (Nursing ethics, 2013)
In relation to the phenomenon of moral distress, this article presents two original perspectives. First, the literature to date reflects a focus on moral distress in an occupational context. In this article, however, the impact of moral distress on siblings is explored. Moral distress is considered in a particular context, stem cell donation, but there are clear insights and implications for wider practice, particularly in life-threatening contexts and situations where live donation enhances the potential for survival. Second, the article represents some progress in relation to creating conceptual clarity. It is suggested that in addition to external and internal moral constraints a further classification of constraint emerges, and that this is useful in teasing out the distinction between moral stress and moral distress. The insights drawn from exploring the experiences of these siblings should enhance the ability to pre-empt and ameliorate potential distress and, ultimately, reduce harm.